The Effect Of Education Through Diary Stunting Prevention Against Strengthening Mother's Knowledge In A Family Camp Of High Quality Charity (A Case Study On The Tribe Of Ahe) - Handini, Lail; Elly Trisnawati; Marlenywati, Marlenywati; Indah Budiastutik (Sean Institute, 2023)
Bengkayang is a district contributing to stunting cases in West Kalimantan, at 30.1% by 2022. The figure has increased compared to the previous year. The majority of the population in this district is the Ahe Dayak tribe, with an average level of secondary to lower education, i.e., no SD, SD, or SLTP graduates. It can affect public understanding, especially among young mothers, of stunting prevention efforts. One of the priority stunting villages in the district is Tumiang Village, which is in the category of Quality Family Village (Kampung KB) with remote access to health services. These factors are determinants of the intensity of health services from the local health force, so it is necessary to make an effort to improve education for young mothers in the prevention of stunting. The study aims to analyze the impact of education through the Stunting Prevention Diary on the improvement of Mother Balita's knowledge in Quality Family Village. The design used was quasi-experimental, with a one-group pretest and posttest. Samples of as many as 30 mothers who have news and are in the village of Tumiang Samalantan Prefecture were taken by purposive sampling. The measurement was done twice over a month of intervention using the Stunting Prevention Diary media. The data was analyzed using a pair T test (α = 95%). The results of the study showed that the majority of young mothers are unemployed (playing as a householder of 53.5%), the job of the head of the family is a farmer/manager/garden worker (80%), the educational level of the mother is SLTP and SLTA (36.7%), and the family income under UMK Bengkayang district was 70%. The knowledge score of the respondents increased from 9.40 to 12.83. The intervention provided is educational through the media. Diary Prevention Stunting is effective in improving the knowledge of the mother of the newborn. Thus, it can be concluded that the education of stunting prevention using the media Diary stunting prevention has an influence on the improvement of mothers' knowledge and can be used as one of the examples of health promotion efforts in order to accelerate the decline in stunting in Bengkayang district.